High Throughput Screening: Benchmarking Computational Alchemy for Carbide, Nitride, and Oxide Catalysts (Adv. Theory Simul. 4/2019). Issue 4 (4th April 2019) - Griego, Charles D.; Saravanan, Karthikeyan; Keith, John A.
Abstract : The cover represents atomic scale structures of different materials (carbides, nitrides, and oxides) coming out of a screen of a computer in a scientific laboratory. The computational alchemy procedure reported in article number1800142 by Charles D. Griego, Karthikeyan Saravanan, and John A. Keith leverages a few Kohn‐Sham density functional theory calculations for high‐throughput screening of novel material catalysts with minimal computational effort.